Starboy: Konstruksi Identitas Mahasiswa Melalui Perilaku Konsumtif Barang Branded - Rabiatun Adawiah Bunga Eja (Emik, 2025)
The consumption of branded items has shifted from mere functional needs to symbols of social status, lifestyle, and personal identity expression. This study highlights the emergence of the term starboy among male students a label often associated with luxury, digital presence, and the use of branded products as a form of popular culture that shapes consumption patterns both within campus social settings and across social media platforms. While previous studies have largely emphasized the relationship between consumer lifestyles and the general use of branded goods, this article focuses more specifically on how university students construct their identities through branded products. This research employs a descriptive qualitative approach and was conducted in Makassar. The study involved nine informants (aged 18 to 23 years), selected based on criteria as active male undergraduate students who use branded goods, follow fashion trends, and display consumerist behaviors related to branded product purchases. Data were collected through observation and in-depth interviews. The study reveals that students have diverse perspectives on the concept of starboy. They understand starboy as a label reflecting a luxurious lifestyle. They view the starboy as someone who is not only fashionable but also capable of attracting attention and gaining recognition in campus and social media environments. Moreover, the consumer behavior of students who adopt the starboy style is related to the use of branded goods, which is based on both objective and subjective assessments. However, purchasing decisions are often dominated by subjective motives rather than rational considerations. Factors driving this consumer behavior include exposure to social media, which showcases a luxurious lifestyle and popular culture, the influence of peer groups possessing branded items, and personal motivations such as self-reward buying items as a form of self-appreciation. Additionally, there is an awareness of their consumer practices, which has implications for efforts to manage shopping habits more effectively. In conclusion, the consumption of branded goods among male students in Makassar who adopt the starboy style serves as a symbolic medium for constructing identity and social status, while also providing space for reflection on more rational consumer behaviors.